The Effect of Memory in Inducing Pleasant Emotions with Musical and Pictorial Stimuli. Issue 1 (December 2018) - Maksimainen, Johanna; Wikgren, Jan; Eerola, Tuomas; Saarikallio, Suvi
Abstract Music is known to evoke emotions through a range of mechanisms, but empirical investigation into the mechanisms underlying different emotions is sparse. This study investigated how affective experiences to music and pictures vary when induced by personal memories or mere stimulus features. Prior to the experiment, participants were asked to select eight types of stimuli according to distinct criteria concerning the emotion induction mechanism and valence. In the experiment, participants (N = 30) evaluated their affective experiences with the self-chosen material. EEG was recorded throughout the session. The results showed certain interaction effects of mechanism (memory vs. stimulus features), emotional valence of the stimulus (pleasant vs. unpleasant), and stimulus modality (music vs. pictures). While effects were mainly similar in music and pictures, the findings suggest that when personal memories are involved, stronger positive emotions were experienced in the context of music, even when the music was experienced as unpleasant. Memory generally enhanced social emotions specifically in pleasant conditions. As for sadness and melancholia, stimulus features did not evoke negative experiences; however, these emotions increased strongly with the involvement of memory, particularly in the condition of unpleasant music. Analysis of EEG-data corroborated the findings by relating frontomedial theta activity to memory-evoking material.